The modulus of elasticity: Islam, art and populism in postcolonial, securitized Europe. Issue 2 (January 2018) - Scott-Baumann, Alison
Abstract : Current public and political interactions are becoming increasingly populist, illustrating the great success of an approach that creates the belief that majority populations in Europe and USA are in fact beleaguered, as if they are a minority threatened by those considered allochthonous. People's democratic agency is thereby silenced and weakened. The Institut des Cultures d'Islam (ICI) deflates populism's boast by bringing individuals, ideas, and artefacts together in a local setting to deconstruct these generalities by being together. The methodology of this paper is to use philosophy, literary analysis, social theory, and physics to analyse the ICI as the same breathed space in which many interpersonal ruptures can be made possible, recognized as such, and then averted. There are ambiguities of difference and of the positive tensions that can be created by bringing culte (worship) and culture (art) together. This article proposes that the modulus, the measure of (human) rigidity (and flexibility), can be used to analyse what happens at the ICI and to consider how outsider 'experts' can both approach this space and also accept that their grasp of what is at stake within it will remain partial.